Improved communication, understanding of risk perception and ethics related to ionising radiation. (6th June 2016) - Perko, Tanja; Raskob, Wolfgang; Jourdain, Jean-Rene
Abstract: In Europe today, institutions, media and the general public exchange information about ionizing radiation and associated risks. However, communication about ionising radiation with the general public has to be further improved, as has been previously highlighted by international responses to the 2011 accident in Japan. This article reports the main activities and findings in this field from the following three FP7 projects: EAGLE, PREPARE and OPERRA and discussed by a broad spectrum of stakeholders at the conference RICOMET 2015. These projects, among other aims, also investigate how communication about ionising radiation in different fields could be improved and harmonised, how radiological risks are perceived, how to encourage ethical considerations in all fields of nuclear applications and what kind of transdisciplinary research is needed. The projects relate to several domains; the first relates to education, training and communication, the second to nuclear emergency preparedness and response, and the third to research and development in the radiation protection field. Incorporation of stakeholder engagement activities such as the RICOMET conference broadens social and ethical aspects and takes them into account during coordination activities as well as during core scientific and nuclear research and development performed in the projects. These activities offered opportunities for moving closer to a citizen-centred ideal of risk communication in particular and nuclear research and development in general.